Big Tech, the platform economy and the European digital markets - Volker Brühl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
Digital platforms have become an important part of the digital economy by facilitating transactions between large numbers of users and by fostering innovation on collaborative platforms. In combination with technical platform services, some platform operators have managed to create powerful ecosystems that create network externalities and benefit from economies of scale and economies of scope. It is striking that, due to the specific economic drivers of the digital infrastructure, platform-based or platform-related services are dominated by a select number of global players. Most of the global platform operators are headquartered in the US, including Alphabet, Amazon, Apple, Meta and Microsoft, also known as the "Big 5". Some are located in Asia (e.g. Alibaba, Tencent). In Europe there are only a limited number of platform operators with a small market share. [...]
urn:nbn:de:hebis:30:3-691406
Keywords: L14; L22; L25; 330